Castanhais & quilombos do Alto Trombetas: uma proposta de justiça socioambiental - ALVES, Felipe Souto (Universidade Federal do Oeste do Pará, 2023)
Studies prove that the extraction of Brazil nuts, although it helps in the regeneration of Brazil nuts land, has not been such a profitable activity for the quilombolas of Alto Trombetas. In this context, this dissertation analyzes the production chain of Brazil nuts, following parameters of socio-environmental justice in this bioeconomy. The methodologies used were: a literature review, a description of the chain through valuelinks and an analysis of the speeches of the actors involved. So, this work dares to simulate a production chain, so that the purchase and sale values for the kilogram of Brazil nuts have greater equity between the actors in the chain. The proposal follows a fair trade model and exposes some strategies to maintain coloniality and injustices present in the production chain of Brazil nuts from the nut groves of the Alto Trombetas’s quilombos. Thus, it concludes that there is a mutual relationship between the traditional quilombola way of life and the chestnut trees, which is fundamental for the existence of the production chain. And that there is a need for greater participation by extractivists in the governance of the chain to balance the distribution of profitability, to adapt the concept of fair trade.